Medical devices: from licensing to coverage. highlights from Argentina, Brazil, Colombia and Mexico. (1st November 2016) - Rey-Ares, Lucila; Hernández-Vásquez, Akram; Garay, Osvaldo Ulises; Pichon Riviere, Andrés; Garcia Marti, Sebastián; Gilardino, Ramiro; Cabra, Hermilio Arturo; Augustovski, Federico
ABSTRACT: Objectives : To describe and compare the requirements for medical devices licensing and reimbursement in four Latin-American countries. Methods : We conducted a literature search in major databases, and generic Internet engines, and interviewed key informants. Results : We included all publications describing regulation and/or coverage and enriched them with key informant's interviews. We found that licensing processes are similar. The decision-making process for coverage is not formally different than the one used for drugs. Although countries differ, Brazil, Colombia and Mexico have an explicit process informed by Health Technology Assessment. In general, coverage policies are defined for procedures and don´t specify device brand or model, and for that reason they may reimburse without explicit one by one device evaluation. Conclusions : The process for licensing and reimbursement is broadly similar but less stringent than that for drugs. It allows the adoption of medical devices without individual comprehensive assessment.